From dynastic cycle to eternal dynasty: The Japanese notion of unbroken lineage in Chinese and Korean constitutionalist debates, 1890–1911 - Moniz Bandeira, Egas (Global Intellectual History, 2022)
This paper shows that the poltical and social upheavals of the late nineteenth and early twentieth century in East Asia also engendered novel ideas and cross-national debates about dynasties in East Asia. The Japanese notion of a ‘line of Emperors unbroken for ages eternal’ became the most emblematic provision of the Meiji Constitution. Under the impact of the Japanese model and of modern discourses on constitutional law, the Qing and Korean governments sought to radically transform traditional concepts of dynastic rule by constitutionally perpetuating the ruling dynasties. However, the notion of an unbroken lineage proved to be highly ambiguous outside of the Japanese context. Its adoption in the Qing constitutional outline of 1908 met with considerable resistance and nurtured suspicions that ‘constitutional preparation’ was only serving the Court's selfish interests. But under the surface, the Japanese model of an unbroken ruling dynasty was de-dynasticised and applied to the notion of constitution and even to the State itself. As the Confucian classics were no longer sufficient to legitimise rulership, the new notion of an eternal fundamental law fused with traditional notions of permanent principles of governance and helped establishing written constitutional charters as ineluctable elements of the modern nation-state in East Asia.
Created from Fastlane, Scopus look-up
Keywords: bansei ikkei; constitutions; Dynasties; Qinding xianfa dagang; Taehan’guk kukche